2005
DOI: 10.1063/1.2108123
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent electronic structure of ultrathin SrRuO3 films studied by in situ photoemission spectroscopy

Abstract: In situ thickness-dependent photoemission spectroscopy (PES) has been performed on SrRuO3 (SRO) layers deposited on SrTiO3 substrates to study the structure-induced evolution of the electronic structure. The PES spectra showing the existence of two critical film thicknesses reveal that a metal-insulator transition occurs at a film thickness of 4–5 monolayers (ML) and the evolution of Ru 4d-derived states around the Fermi level (EF) saturates at about 15 ML. The observed spectral behavior well matches the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 24 publications
10
137
6
Order By: Relevance
“…22,28,32 Here we first revisit the LSDA with our own calculations, with an emphasis on understanding discrepancies between the experimental measured photoemission results 18,19 and the calculated LSDA electronic structure of the orthorhombic material. We then extend our study to the two "beyond-LSDA" approaches to examine correlation effects in bulk Pbnm and Pm3m SrRuO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,28,32 Here we first revisit the LSDA with our own calculations, with an emphasis on understanding discrepancies between the experimental measured photoemission results 18,19 and the calculated LSDA electronic structure of the orthorhombic material. We then extend our study to the two "beyond-LSDA" approaches to examine correlation effects in bulk Pbnm and Pm3m SrRuO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been demonstrated that metallic SrRuO 3 can be transformed into an insulating state by growing films thinner than five monolayers on SrTiO 3 substrates. 18 It was also found that the Curie temperature decreases with reduced film thickness, along with the disappearance of strong ferromagnetic order. Photoemission experiments show a shift in the spectral weight to the incoherent peak features in the spectra, suggesting that these effects are a result of changes in electron-electron correlation effects.…”
Section: E Thin Filmsmentioning
confidence: 97%
See 1 more Smart Citation
“…19 and 20, or soft x-ray PES is used. [21][22][23][24] Since it is well known that PES is highly surface sensitive, the cleaning of ex situ prepared specimens by applying heating or scraping techniques may somehow affect the surface and thus further complicate the investigation of intrinsic electronic structure in SrRuO 3 . Moreover, Siemons et al 19 have concluded that a tiny change in ruthenium stoichiometry may have a fairly considerable effect on the PES spectrum, indicating a highly stoichiometry-dependent degree of correlation for this material.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one should also take into account the fact that physical properties of this perovskite are sensitive to the strain 26 and thin film thickness. 24 Having in mind that all these factors may influence the experiment, one should be very careful while making rigorous comments about electronic structure in SrRuO 3 . It is evident that interpretation of experimental results is highly dependent on accurate theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%